2020
DOI: 10.1016/j.conctc.2019.100495
|View full text |Cite|
|
Sign up to set email alerts
|

Intestinal-level anti-inflammatory bioactivities of catechin-rich green tea: Rationale, design, and methods of a double-blind, randomized, placebo-controlled crossover trial in metabolic syndrome and healthy adults

Abstract: Metabolic endotoxemia initiates low-grade chronic inflammation in metabolic syndrome (MetS) and provokes the progression towards more advanced cardiometabolic disorders. Our recent works in obese rodent models demonstrate that catechin-rich green tea extract (GTE) improves gut barrier integrity to alleviate the translocation of gut-derived endotoxin and its consequent pro-inflammatory responses mediated through Toll-like receptor-4/nuclear factor κB (TLR4/NFκB) signaling. The objective of this clinical trial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 65 publications
(92 reference statements)
1
45
0
Order By: Relevance
“…Immediately after the SESI-HRMS analysis of ampicillin treatment, 1 mL of microbial cultures was placed into 2 mL tubes and kept at −80 °C until further metabolite extraction. The previously published method was modified for the analysis of C2–C7 volatile fatty acids from the liquid cultures [ 53 ]. Briefly, the collected supernatant was centrifuged at 14,000 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Immediately after the SESI-HRMS analysis of ampicillin treatment, 1 mL of microbial cultures was placed into 2 mL tubes and kept at −80 °C until further metabolite extraction. The previously published method was modified for the analysis of C2–C7 volatile fatty acids from the liquid cultures [ 53 ]. Briefly, the collected supernatant was centrifuged at 14,000 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Another important aspect is "gut-lung" crosstalk, in recent times this phenomenon has gained lot of attention and it is widely recognized that an ideal gut microenvironment is essential for a balanced immune response not only for gastrointestinal track but also for maintaining respiratory homeostasis (41). Experimental and clinical evidences have indicated that host stress response activates macrophages and neutrophils in alveolar cells, leading to increase in pro-inflammatory cytokines and catecholamines (42). This signal is strongly correlated with growth and virulence of bacterial community like streptococcus pneumonia, klebsiella pneumonia perpetuating alveolar inflammation (42).…”
Section: Tea Polyphenols and Alkaloids Role In Innate Immunitymentioning
confidence: 99%
“…Experimental and clinical evidences have indicated that host stress response activates macrophages and neutrophils in alveolar cells, leading to increase in pro-inflammatory cytokines and catecholamines (42). This signal is strongly correlated with growth and virulence of bacterial community like streptococcus pneumonia, klebsiella pneumonia perpetuating alveolar inflammation (42). This change in the inflamed lungs also leads to "gut dysbiosis" altering gut microbiota.…”
Section: Tea Polyphenols and Alkaloids Role In Innate Immunitymentioning
confidence: 99%
See 2 more Smart Citations